2018
DOI: 10.17113/ftb.56.02.18.5390
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Conversion of Sugar Beet Pulp: A Comparison of Simultaneous Saccharification and Fermentation and Separate Hydrolysis and Fermentation for Lactic Acid Production

Abstract: SummaryThis study compares the efficiency of lactic acid production by separate hydrolysis and fermentation (SHF) or simultaneous saccharification and fermentation (SSF) of sugar beet pulp (SBP), a by-product of industrial sugar production. In experiments, SBP was hydrolyzed using 5 commercial enzymes. A series of shake flask scale fermentations and was conducted using 5 selected strains of lactic acid bacteria (LAB). The differences in the activities of the enzymes for degrading the principal SBP components w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 40 publications
(43 reference statements)
4
23
0
Order By: Relevance
“…As the major by-product of the brewing industry, accounting for around 25% of the total product [15,16], brewer's spent grain is both low in cost and unaffected by seasonal variations. Similarly, sugar beet pulp is the major by-product of sugar beet processing, with 1.5 Mt generated per 30 Mt of sugar beet [17,18]. The very low lignin content of just 2% (Table 2), renders sugar beet pulp a particularly desirable feedstock.…”
Section: Feedstockmentioning
confidence: 99%
“…As the major by-product of the brewing industry, accounting for around 25% of the total product [15,16], brewer's spent grain is both low in cost and unaffected by seasonal variations. Similarly, sugar beet pulp is the major by-product of sugar beet processing, with 1.5 Mt generated per 30 Mt of sugar beet [17,18]. The very low lignin content of just 2% (Table 2), renders sugar beet pulp a particularly desirable feedstock.…”
Section: Feedstockmentioning
confidence: 99%
“…These monosaccharides can successfully be used as sources of sugars for microorganisms (e.g., lactic acid bacteria, yeasts, fungi, etc.) [8][9][10][11] or as substrates in chemical syntheses, e.g., for the production of fuels (bioethanol, methane, hydrogen), solvents, polymers, etc. [4,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by Rana et al ., who concluded that SSF turned out to be more efficient than SHF, despite a suboptimal temperature being employed for the enzyme hydrolysis. Using the SSF strategy, cellulases inhibition can be avoided . Moreover, low levels of glucose in the medium reduce the risk of carbon catabolic repression and so other sugars such as arabinose might be used for lactic acid production.…”
Section: Resultsmentioning
confidence: 99%